2005
DOI: 10.1074/jbc.m412938200
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin/γ-Secretase-mediated Cleavage of the Voltage-gated Sodium Channel β2-Subunit Regulates Cell Adhesion and Migration

Abstract: The voltage-gated sodium channel ␤2-subunit (␤2) is a member of the IgCAM superfamily and serves as both an adhesion molecule and an auxiliary subunit of the voltage-gated sodium channel. Here we found that ␤2 undergoes ectodomain shedding followed by presenilin (PS)-dependent ␥-secretase-mediated cleavage. 12-OTetradecanoylphorbol-13-acetate treatment or expression of an ␣-secretase enzyme, ADAM10, resulted in ectodomain cleavage of ␤2 in Chinese hamster ovary cells. Subsequent cleavage of the remaining 15-kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 67 publications
2
140
0
Order By: Relevance
“…DAPT treatment phenocopies mind bomb mutants, which inactivate an E3 ubiquitin ligase necessary for efficient Notch signaling (Itoh et al, 2003) and is reversed by expression of processed Notch (Geling et al, 2002). Although DAPT blocks processing of other ␥-secretase targets such as ErbB4 (Sardi et al, 2006), amyloid precursor protein (Dovey et al, 2001), or sodium channel ␤ subunit (Kim et al, 2005), the similarities in its effect on HC production after Notch loss of function leads us to conclude that DAPT is most likely affecting this pathway. Although DAPT appears to have no differential specificity to different forms of presenilin (Zhao et al, 2008), there may be other ␥-secretases still functioning to modulate lateral line development after DAPT treatment.…”
Section: Notch Signaling Differentially Regulates Proliferation Of Sumentioning
confidence: 99%
“…DAPT treatment phenocopies mind bomb mutants, which inactivate an E3 ubiquitin ligase necessary for efficient Notch signaling (Itoh et al, 2003) and is reversed by expression of processed Notch (Geling et al, 2002). Although DAPT blocks processing of other ␥-secretase targets such as ErbB4 (Sardi et al, 2006), amyloid precursor protein (Dovey et al, 2001), or sodium channel ␤ subunit (Kim et al, 2005), the similarities in its effect on HC production after Notch loss of function leads us to conclude that DAPT is most likely affecting this pathway. Although DAPT appears to have no differential specificity to different forms of presenilin (Zhao et al, 2008), there may be other ␥-secretases still functioning to modulate lateral line development after DAPT treatment.…”
Section: Notch Signaling Differentially Regulates Proliferation Of Sumentioning
confidence: 99%
“…The processed C-terminal fragment of β2 and β4 has been reported to be associated with cell adhesion, migration, and morphogenesis in neuronal cells as well as regulation of the expression level of the neuronal sodium channel Na V 1.1 (44)(45)(46). Thus, p.Trp179X β1B may result in absence of functions depending on the generation of a β subunit C-terminal fragment by BACE1.…”
Section: Figurementioning
confidence: 99%
“…51 Mutations in both a-or b-subunits have been associated, among other disorders, with epilepsy. 52 46,55 Five years later, BACE1 cleavage sites were mapped in the b2 subunit, which plays an important role in hippocampus and cortex. 56 Our group then showed that proteolysis of b2 by BACE1 caused a leftward shift in the voltage dependence of reconstituted Na v 1.2 current, demonstrating that the cleavage bears significance for channel gating.…”
Section: Bace1 and Neuronal Na V Channelsmentioning
confidence: 99%